(untitled) (SAARC Journal of Agriculture, 2022)
A field study was undertaken at Bangladesh Agricultural University, Mymensingh during the season November 2017 to April 2018 to evaluate the effects of plant × row spacings on yield and yield contributing traits of two Boro rice varieties. Two rice varieties viz., BINA dhan-10 and BRRI dhan28 were sown in five plant spacings viz. 25 cm × 15 cm, 25 cm × 25 cm, 30 cm × 30 cm, 35 cm × 35 cm, 40 cm × 40 cm in randomized completely block design with factorial fashion with three replications. Growth performances, yield contributing characters and yield were significantly influenced by varieties and plant spacings. The highest grain yield (8.75t ha-1), straw yield (11.56 t ha-1), biological yield (20.31 t ha-1) and harvest index (43.05 %) were obtained from the variety BINA dhan- 10 sown at planting spacing of25 cm × 15 cm. More number of total tillers hill-1(14.75) and number of effective tiller hill-1 (12.87) were recorded from the variety BINA dhan-10 sown at planting spacing 40 cm × 40 cm. Based on the present study it is suggested that BINA dhan-10 may be grown under 25 cm × 15 cm in order to get maximum grain yield for Boro rice cultivation. SAARC J. Agric., 19(2): 95-106 (2021)